Factors influencing short-term solvency in Indian automobile industry - Abey, Joji; Velmurugan, R (International Journal of Engineering and Technology, 2018)
The automobile industry in India occupies a vital role in the economic progress of the nation. The reputation of any industry depends on its liquid position, which helps a company in settling their dues in time. Liquidity denotes to the firmâ€™s capacity to pay their outstanding dues. The article considers liquidity position of automobile industry by employing correlation and regression test. The data required for the study is secondary in nature. The required data are collected from Capitaline database for the period ranging between 2008 and 2017. The collected data is analyzed by making use of correlation and regression. The result reveals that liquidity position of a company depends on age, inventory turnover ratio, dividend payout ratio and leverage.Â Â